Fine Root Growth of Black Spruce Trees and Understory Plants in a Permafrost Forest Along a North-Facing Slope in Interior Alaska - Noguchi, Kyotaro; Matsuura, Yojiro; Morishita, Tomoaki; Toriyama, Jumpei; Kim, Yongwon (Frontiers in Plant Science, 2021)
Permafrost forests play an important role in the global carbon budget due to the huge amounts of carbon stored below ground in these ecosystems. Although fine roots are considered to be a major pathway of belowground carbon flux, separate contributions of overstory trees and understory shrubs to fine root dynamics in these forests have not been specifically characterized in relation to permafrost conditions, such as active layer thickness. In this study, we investigated fine root growth and morphology of trees and understory shrubs using ingrowth cores with two types of moss substrates (feather- and Sphagnum mosses) in permafrost black spruce (Picea mariana) stands along a north-facing slope in Interior Alaska, where active layer thickness varied substantially. Aboveground biomass, litterfall production rate and fine root mass were also examined. Results showed that aboveground biomass, fine root mass and fine root growth of black spruce trees tended to decrease downslope, whereas those of understory Ericaceae shrubs increased. Belowground allocation (e.g. ratio of fine root growth / leaf litter production) increased downslope in both of black spruce and understory plants. These results suggested that, at lower slope, belowground resource availability was lower than at upper slope, but higher light availability under open canopy seemed to benefit growth of the understory shrubs. On the other hand, understory shrubs were more responsive to the moss substrates than black spruce, in which Sphagnum moss substrates increased fine root growth of the shrubs as compared with feather moss substrates, whereas the effect was unclear for black spruce. This is probably due to higher moisture contents in Sphagnum moss substrates, which benefited growth of small diameter (high specific root length) fine roots of understory shrubs. Hence, contribution of understory shrubs to fine root growth was greater at lower slope than at upper slope, or in Sphagnum- than in feather-moss substrates in our study site. Taken together, our data show that fine roots of Ericaceae shrubs are a key component in belowground carbon flux at permafrost black spruce forests with shallow active layer and/or with Sphagnum dominated forest floor.